Conservation genetics of otters: Review about the use of non-invasive samples - Aristizabal Duque, Sandra L.; Orozco-Jimenez, Luz Y.; Zapata-Escobar, Carolina; Palacio-Baena, Jaime A. (THERYA, 2018)
Wild population management programs require determining some fundamental aspects for conservation, including population structure, flow between populations, evolutionary history and kinship, among others. Since sample collection from wild mammals for DNA extraction is a complex task, conservation genetics has developed non-invasive sampling techniques, which allow obtaining DNA without the need to capture individuals. For the genetic characterization of otter populations, stools are frequently used as source of DNA for amplification of molecular markers (microsatellites, mitochondrial segments and sequences for determining sex) in studies on genetic diversity, phylogeography, population structure and size, among others. This review summarizes the application of non-invasive sampling techniques in genetic studies of otter species. Genetic characterization studies that use stools as source of DNA support the usefulness of this material to get amplified markers in the genotyping of individuals. They also suggest the use of fresh samples and appropriate conservation methods to avoid DNA degradation, as well as quantify the potential errors in genotyping, such as false and null alleles.